From login to loyalty: the mediating role of trust in digital banking readoption - Hassan, Suzana; Bujang, Imbarine; Othman, Nor Azairiah Fatimah; Jati, Muhamad Khodri Kholib (Universiti Teknologi MARA Selangor, 2025)
The digital transformation of Malaysia’s banking sector has reshaped how customers engage with financial services. While the adoption of digital banking surged during the COVID-19 pandemic, sustaining user engagement remains a challenge. Concerns regarding security, usability, and trust have led to hesitancy in continued usage. This study investigates the influence of social influence and facilitating conditions on users’ readoption of digital banking services in Malaysia, a concept examined in conjunction with continuance intention to reflect the theoretical underpinnings of sustained post-adoption behaviour, with trust serving as a mediating variable. Drawing upon the ExpectationConfirmation Model (ECM), the research emphasizes how users' postadoption experiences and expectations shape their behavioral intentions. Using a quantitative design, data were collected from 230 digital banking users and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that social influence significantly enhances trust, which in turn strongly predicts readoption. Facilitating conditions, however, had a weaker direct impact on trust. The results affirm that trust is a central determinant in driving continued engagement with digital financial services. The study offers practical implications for financial institutions by recommending the strengthening of user trust through transparent communication, social proof strategies, and consistent system support. It also contributes theoretically by extending ECM within the context of digital banking readoption in a developing economy.